The Effect of Profitability, Liquidity, and Solvency on Sustainable Reporting with Corporate Governance as Moderating Variable - Baldric Siregar; Niken Betari Muslimah; Dody Hapsoro (Journal of International Conference Proceedings (JICP), 2022)
This study aims to examine the effect of profitability, liquidity, and solvency on sustainable reporting. This study also examines the impact of corporate governance in moderating the effect of profitability, liquidity, and solvency on sustainable reporting. We use data on finance, governance, and sustainability reporting obtained from financial reports and sustainability reports for financial institution companies over 5 years, from 2016 to 2020. We use multiple regression to estimate the research model. Empirical findings show that profitability and liquidity have a positive impact on sustainable reporting. Other findings also show that corporate governance can increase the positive impact of profitability on sustainable reporting.